Law and Disorder: Ontario Catholic Bishops’ Opposition to Gay-Straight Alliances - Callaghan, Tonya D. (Paideusis, 2014)
Originating in the United States, a Gay/Straight Alliance (GSA) is an in-school student club whose focus is on making the school a safe space for lesbian, gay, bisexual, transgender and queer students and their straight allies by raising awareness about, and hopefully reducing, school-based homophobia. The ongoing struggle for GSAs in Canadian Catholic schools is one example of how clashes continue to be played out between Catholic canonical law and Canadian common law regarding sexual minorities. This paper draws upon Foucault’s Discipline and Punish: The Birth of the Prison, and The History of Sexuality Vol. 1: An Introduction to analyze one particularly influential curricular and policy document entitled Pastoral Guidelines to Assist Students of Same-Sex Orientation from the Ontario Conference of Catholic Bishops. This paper posits that Catholic doctrine about non-heterosexuality functions as a Foucaultian Panopticon enabling Catholic education leaders to observe and correct the behaviour of non-heterosexual teachers and students that they deem runs counter to the values of the Vatican. This paper argues that successful resistance to the powerful disciplining regime of the Catholic school is possible.